Modeling the risks of the global customs space - Olha Borysenko; Olena Vasyl'yeva; Olga Katerna; Iuliia Masiuk; Oleg Panakhi (Journal of Risk and Financial Management, 2022)
The influence of globalization processes, the customs space of the country, requires the development and implementation of a transparent state customs policy to ensure security and integration into the space of the higher hierarchical order. The purpose of the study is to form scientific-applied recommendations regarding the development vectors of the customs space of a country in the global environment to improve its risk management system. The main method of study is econometric modeling, namely, canonical analysis in determining the interdependence of sustainable development and customs space. The purpose of the study is to suggest directions for development vectors for a country's customs space that will mitigate various risks. Originally, 174 countries were selected for analysis, but the final sample was formed by 98 countries. According to the results of econometric modeling, it was determined that the following variables have the greatest impact on the customs space: human development index; GDP per capita; corruption perception index; global enabling trade index; environmental performance index; social progress index; global competitiveness index. The findings can be used by public authorities in developing a strategy for reforming the customs system of developing countries, taking into account the risks and challenges of the global environment.
Keywords: 650; risk; customs policy; global customs space; international business